2015
DOI: 10.1210/en.2015-1660
|View full text |Cite
|
Sign up to set email alerts
|

The ERα-PI3K Cascade in Proopiomelanocortin Progenitor Neurons Regulates Feeding and Glucose Balance in Female Mice

Abstract: Estrogens act upon estrogen receptor (ER)α to inhibit feeding and improve glucose homeostasis in female animals. However, the intracellular signals that mediate these estrogenic actions remain unknown. Here, we report that anorexigenic effects of estrogens are blunted in female mice that lack ERα specifically in proopiomelanocortin (POMC) progenitor neurons. These mutant mice also develop insulin resistance and are insensitive to the glucose-regulatory effects of estrogens. Moreover, we showed that propyl pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 60 publications
4
37
0
Order By: Relevance
“…Energy expenditure was also indirectly evaluated as feed efficiency. Consistently with previous reports on stimulatory effects of estrogen on energy expenditure [11, 12], we found that OVX+E treatment significantly increased energy expenditure as indicated by decreased of feed efficiency in WT female mice (Fig. 3E).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Energy expenditure was also indirectly evaluated as feed efficiency. Consistently with previous reports on stimulatory effects of estrogen on energy expenditure [11, 12], we found that OVX+E treatment significantly increased energy expenditure as indicated by decreased of feed efficiency in WT female mice (Fig. 3E).…”
Section: Resultssupporting
confidence: 93%
“…Previously we demonstrated that loss of ERα specifically in POMC neurons (ERα-POMC-KO) leads to chronic hyperphagia and body weight gain [8] and that the anorexigenic effects of estrogen is attenuated in ERα-POMC-KO females [12]. These results indicate that estrogenic regulation on food intake is at least partially mediated by ERα in POMC neurons.…”
Section: Introductionmentioning
confidence: 81%
“…PI3K is a signaling molecule that is activated upon both ERα and ERβ stimulation (Gingerich and Krukoff, 2008; Smith et al, 2013), as well as by other anorexigenic hormones such as leptin and insulin (Hill et al, 2008; Mela et al, 2015; Qiu et al, 2014), within various elements of the hypothalamic feeding circuitry. PI3K signaling in murine POMC neurons plays an important role in the ERα-mediated regulation of appetite and insulin sensitivity (Zhu et al, 2015). It, along with PKC and PKA, are also involved in the G q -mER-mediated uncoupling of other metabotropic, G i/o -linked receptors like the μ-opioid and GABA B receptors from their GIRK channels in POMC neurons (Kelly et al, 2002; Malyala et al, 2008; Qiu et al, 2006).…”
Section: Sex Differences In the Cannabinoid Regulation Of Energy Hmentioning
confidence: 99%
“…Gonadal steroids, known to regulate reproduction, are found to play a role in neuroprotection, energy homeostasis and regulation of diverse cellular, molecular and functional parameters in both neurons and astrocytes [Zhu et al, 2015; Acaz-Fonseca et al, 2014; 2016]. Central inflammatory responses are influenced by sex steroids.…”
Section: – Estrogen and Pi3k Pathway In The Hypothalamus: A Potentimentioning
confidence: 99%
“…In a recent report, Zhu et al [2015] demonstrated that estrogen acts upon estrogen receptor α (ERα) to inhibit feeding in female mice, and the anorexigenic effects of estrogens are blunted in mice with selective deletion of ERα in POMC neurons. Treatment with ERα agonist stimulated PI3K pathway specifically in POMC neurons.…”
Section: – Estrogen and Pi3k Pathway In The Hypothalamus: A Potentimentioning
confidence: 99%